Wildlife Tracking by Telemetry - Machmud Thohari (Department of Forest Resources Conservation and Ecotourism - IPB University, 1989)
There are some difficulties to study wildlife ecology in their natural habitat by using direct methods, especially for the species which have high mobility, or high sensitivity to human, or those which live nocturnal.A radio telemtry technique offers another alternative for studying the ecological aspect of wildlife, covering any species, i.e. big mammals, small mammals, reptiles, amphibians, fishes, birds, etc. The radio telemtry equipment consist of a transmitter radio, a receiver radio and an antenna. The transmitter is attached on an animal which is able to transmit pulsed signals continuously, which can be detected by the receiver radio and antenna. The transmitter is attached on an animal which is able to transmit pulsed signals continuosly, which can be detected by the receiver through the antenna.